Numerical study of non-Newtonian nano-fluid in a micro-channel with adding slip velocity and porous blocks - Rahmati, Ahmad Reza; Derikvand, Mohammad (International communications in heat and mass transfer, 2020)
The investigation of microfluidics heat transfer in recent years has been of great interest to researchers. In studies to improve the thermal performance of micro-devices, the use of nano-fluids, geometric corrections and other parameters have been investigated. In addition to examining the heat transfer of cooling systems, the research of thermodynamics second-law of these systems has been widely studied in recent years. In this study, thermodynamics second law and heat transfer of non-Newtonian nano-fluid in a micro-channel with distributing variable temperature on the wall, the presence and absence of porous blocks and slip velocity with finite volume method (SIMPLE algorithm) have been investigated. Non-Newtonian nano-fluid contains water-CMC as the basis fluid and volume fraction of 3% and 4% nano-particles of TiO2. The current study is reviewed in two sections in the Reynolds number (10−100) and nano-particles volume fraction (3–4). In the first section, it investigates the influence of slip velocity and compares first and second-order models with different slip factor (0–0.1) on heat transfer, fluid flow, entropy generation and exergy losses. The outcomes present that the slip velocity of the first-order increases the mean Nusselt number in the range of 2.02% to 12.48%, and this range is 1.91% to 7.52% for second-order. Also, the first-order and second-order slip velocities reduce the generation rate of frictional entropy by a maximum of 76.2% and 67.43%, respectively. The rate generation of thermal entropy and exergy losses exhibits variable behaviour with Reynolds number. In the second section, the Darcy number (5 × 10−3–5 × 10−5), porosity (0.75–0.95) and thermal conductivity ratio (1–15) with first-order slip velocity are examined. The Nusselt number increases locally by reducing, reducing and enhancing the Darcy number, porosity and thermal conductivity ratio, respectively. The production rate of frictional entropy also increments by more than 800% with reducing Darcy number and porosity.